PENGGUNAAN BAHASA PROKEM DALAM NOVEL AKU, BENCI & CINTA KARYA WULANFADI - Johana, Nadia; Liusti, Siti Ainim (Jurnal Bahasa dan Sastra, 2019)
The purpose of this study is to describe the shape, process of composition, and use of the prokem in the novel Aku, Benci & Cinta by Wulanfadi. This kind of research is qualitative research using a descriptive method. The source of data in this research is sentence or speech of the prokem in the novel. The findings of this study are as follows: (1) the prokem shape in the novel is composed of single words, frolic, reduplication, abreviation, and composition; (2) the prokem formation process in the novel is composed of nasalizing active verb+-in to form an active transitive verb, passive form di+root word+-in, debunking the word, use of other terms, english foreign language speakers, full use of english, and letter changes; and (3) the use of prokem in a novel is composed of bonding function, expressing feelings, invite, mocking, satirize, reassuring conversation, creating a humorous atmosphere, ask, and passing information.Keywords: indonesian slang, Wulanfadi, Aku Benci & Cinta